Genetic and pathological findings in a boy with psoriasis and C3 glomerulonephritis: A case report and literature review. Issue 10 (28th July 2020) - Wei, Lei; Fang, Ye; Cao, Guanghai; Zhang, Shufeng; Tian, Ming; Shen, Qian; Xu, Hong; Liu, Cuihua; Rao, Jia
Abstract: Background: Psoriasis is a chronic inflammatory dermatosis with complex genetic basis supported by family investigation. Renal involvement in psoriasis is sparsely studied and its pathogenesis is still unclear. Methods and Results: We describe the case of a 7‐year‐old boy presented new onset of nephropathy two weeks after a flare‐up of psoriasis. His mother had a long history of psoriasis without abnormal urinalysis records. The case showed non‐nephrotic range proteinuria, microscopic hematuria without any other abnormal results including renal function, complement cascade, and ultrasound. Renal pathological demonstrated the diagnosis of C3 glomerulonephritis (C3GN) showing mesangial proliferative glomerulonephritis with C3 staining only, effacement of podocyte process and intramembranous electron dense deposit by electric microscopy. Parent‐child trio WES performed to screening the common variants of psoriasis susceptibility locus and also the rare variants associated with C3GN. We identified a missense single nucleotide polymorphism of CARD14 (*607211, rs34367357, p.Val585Ile) carried by the proband and his mother. Meta‐analysis proved the association of rs34367357 and psoriasis ( p  = 0.006, OR = 1.23). A hemizygouse mutation of CLCN5 (*300008, c.1904A＞G, p.Asn635Ser) was identified for diagnosis of Dent disease (*300009). Conclusion: The case highlights the genetic study is necessary to facilitate disease differentiation in new onset of nephropathy with psoriasis in children. Abstract : A case of a 7‐year old boy presented new onset of nephropathy two weeks after a flare‐up of psoriasis. Pathological findings and genetic study identified the diagnosis of C3 glomerulonephritis with psoriasis accompanied by Dent disease.